The impact of physical activity and resistant starch on gut fermentation - Kim, Jiyoung (Kansas State University, 2016)
Purpose: Physical activity (PA) and resistant starch (RS) beneficially affect metabolic health. However, their combined effects on gut health are poorly understood. The purpose of this thesis was to investigate the combined effects of PA and RS via breath hydrogen production and blood glucose responses and directly learn about the research process. Methods: Twenty subjects with no reported symptoms of metabolic diseases participated in this thesis project. Subjects wore accelerometers to determine PA status, and were then stratified into two groups: less active or more active. Once enrolled and stratified into groups based on PA assessment, subjects came to the laboratory on two more occasions to eat a standardized energy dense test meal with a lemonade beverage. The beverage contained different doses (5 g or 25 g) of RS type 4. On each test day, breath hydrogen was collected at baseline through the sixth hour at hour intervals through the fourth hour. Between hours four and six, the breath samples were collected every 30 minutes. Blood glucose samples were collected at baseline before the meal and then 15, 30, 45, 60, 90, and 120 minutes after beginning to eat the meal. Results: The incremental areas under the curve for glucose were not different between PA groups or RS dose (p>0.05). The area under the curve values for breath hydrogen were not different (p>0.05) between groups or doses of PA and RS, respectively. Conclusion: These results indicate that acute assessments of gut fermentation in generally healthy participants, as assessed by postprandial breath hydrogen production, requires more than six hours of assessment to determine differences between treatments and levels of physical activity.
Keywords: Clinical trials; Dietary fiber; Physical activity; Resistant starch; Fermentation; Diabetes; Microbiota; Nutrition (0570)